Pharmacokinetics, safety, tolerability, and antiviral activity of dolutegravir dispersible tablets in infants and children with HIV-1 (IMPAACT P1093): results of an open-label, phase 1–2 trial. Issue 5 (May 2022) - Ruel, Theodore D; Acosta, Edward P; Liu, Jessica P; Gray, Kathryn P; George, Kathleen; Montañez, Nicole; Popson, Stephanie; Buchanan, Ann M; Bartlett, Mattie; Dayton, Dale; Anthony, Patricia; Brothers, Cynthia; et al.
Summary: Background: Safe and potent antiretroviral medications in child-friendly formulations are needed to treat young children living with HIV-1. We aimed to select dosing for a dispersible tablet formulation of dolutegravir that achieved pharmacokinetic exposures similar to those in adults, and was safe and well tolerated in young children. Methods: International Maternal Pediatric Adolescent AIDS Clinical Trial (IMPAACT) P1093 is a phase 1–2 ongoing multicentre, open-label, non-comparative study of dolutegravir. A 5 mg dispersible tablet formulation of dolutegravir was studied in children aged 4 weeks to less than 6 years old, weighing at least 3 kg, with HIV RNA of greater than 1000 copies per mL and no previous treatment with integrase strand transfer inhibitor recruited from IMPAACT clinical research sites in Africa, the Americas, and Asia. Doses were selected on the basis of intensive pharmacokinetic evaluation on days 5–10, with safety and tolerability assessed up to 48 weeks. The primary objectives of this study are to evaluate the pharmacokinetics of dolutegravir in combination with optimised background therapy and to establish the dose of dolutegravir that achieves the targeted 24-h trough concentration and 24-h area under the curve for infants, children, and adolescents with HIV-1, to establish the safety and tolerability of dolutegravir at 24 and 48 weeks, and to select a dose that achieves similar exposure to the dolutegravir 50 mg once daily dose in adults. This analysis included participants treated with the proposed dose of dolutegravir dispersible tablets in two stages for each of three age cohorts. This trial is registered at ClinicalTrials.gov (NCT01302847 ) and is ongoing. Findings: We recruited 181 participants from April 20, 2011, to Feb 19, 2020; of these, 96 received dolutegravir dispersible tablets. This analysis included 73 (35, 48% female) participants who received the final proposed dose with median (range) age of 1 year (0·1 to 6·0), weight (minimum–maximum) of 8·5 kg (3·7 to 18·5), plasma HIV-1 RNA concentration of 4·2 log10 copies per mL (2·1 to 7·0), and CD4% of 24·0% (0·3 to 49·0); 64 (87·7%) were treatment-experienced. The selected dose within each age cohort (≥2 years to <6 years, ≥6 months to <2 years of age and ≥4 weeks to <6 months) achieved geometric mean trough (ng/mL) of 688, 1179, and 1446, and 24 h area-under-the-curve (h·mg/L) of 53, 74, and 65, respectively. No grade 3 or worse adverse events were attributed to dolutegravir. Interpretation: In this study, the proposed once daily dosing of dolutegravir dispersible tablets provided drug exposures similar to those for adults, and was safe and well tolerated. These data support the use of dolutegravir dispersible tablets as first-line or second-line treatment for infants and children aged less than 6 years living with HIV-1. Funding: National Institute of Allergy and Infectious Diseases, the Eunice Kennedy Shriver National Institute of Child Health and Human Development, the National Institute of Mental Health, and ViiV Healthcare–GlaxoSmithKline.